Lack of Children's Activity in Learning And Teaching English Class7 MTS Yasmi Duri - Sembiring, Liasna Br (International Journal of Business and Information Technology, 2024)
Inactivity in learning is a problem that is often faced by students in class. This problem can hinder students' ability to understand lessons and produce good academic performance. Therefore, a study was conducted to analyze the factors that contribute to students' learning inactivity and apathy in the classroom. Several factors were found including unattractive teaching methods, unsupportive learning environment, lack of student involvement in the learning process, and personal factors such as lack of motivation and self-confidence. In order to overcome this problem, strategies are needed that can increase student involvement in learning, such as using technology and social media, teaching more creatively, increasing parental support, and developing motivational and self-regulation strategies. By implementing these strategies, students are expected to be more active and involved in the learning process so that they can achieve their true learning potential. What will be discussed here is the 7th grade students at MTS Yasmi Duri in learning English.